Assessment of Macroinvertebrates as Bioindicators of Water Quality in the Littoral Zone of Lake Mainit, Philippines - Paylangco, Jesiel Cris Chatto; Gamalinda, Eve Fernandez; Seronay, Romell Alope; Jumawan, Joycelyn Cagatin (Asian Journal of Biological and Life Sciences, 2020)
Water quality in the lake littoral zone influence habitat complexity. This study determined the relationships of macroinvertebrates in response to water physicochemical parameters in ten littoral zone stations across four municipalities of Lake Mainit Philippines. Macroinvertebrates were collected following the standard protocol for littoral areas with modifications and taxa groupings were assigned based on sensitivity to pollution. Water Quality Index (WQI) from the identified bioindicator species was computed. Results revealed that all physicochemical parameters of the ten sampling stations passed the water quality standard set by DAO 2016, except for the pH and temperature readings of Mansayao and Tagbuyawan. Out of 20, 924 macroinvertebrates collected, 16 species were identified from 13 families. Station Mansayao exhibited higher species diversity (H’=1.98). No EPT (Ephemeroptera, Plecoptera, Trichoptera) species were observed across stations. Most of the macroinvertebrates collected were under Taxa 2 (50%) and Taxa 3 (50%), the presence of which, indicates moderate to poor water quality. The WQIs range from 3.1-3.7, which means the stations have “rather dirty to average” and “dirty water”, except for the San Roque station (WQI=2.5), which showed a polluted water quality. Of the 16 species of macroinvertebrates collected, only ten species showed moderate positive association to pH, dissolve oxygen, temperature and Total Dissolved Solids. Littoral zones of the Lake Mainit still support and harbor a variety of aquatic macroinvertebrates. However, the abundance of pollutiontolerant species indicates a declining water quality due to the influence of anthropogenic activities surrounding the lake.
Keywords: Bioindicators; Lake littoral zone; Macroinvertebrates; Water quality; Diversity; Taxa grouping